Synthesis of A-CD Estrogens with Potential for Hormone Replacement Therapy. Isolation of Sesquiterpene Lactones from Neurolaena lobata and Diterpenoids from Leretia cordata - Choueiri, Christine (Université d'Ottawa / University of Ottawa, 2013)
The use of estrogen supplements by postmenopausal women has been associated with increased risks of uterine and breast cancer. There are two possible mechanisms of toxicity: estradiol can promote breast cancer cell proliferation through estrogen receptor-α (ERα) and get metabolized to genotoxic ortho-quinones. The first part of this thesis describes the synthesis of a new series of non-carcinogenic A-CD estrogen agonists for hormone replacement therapy (HRT) with either the cis (1) or the trans (2) CD-ring junction. These compounds closely resemble estradiol (3) but lack the B-ring, allowing the ligands to adopt different conformation inside the binding pocket. One example of BC-spirolactone estrogen (4) is also described. Binding affinity and selectivity to both estrogen receptor subtypes ERα and ERβ were determined primarily by their Relative Binding Affinities (RBAs) and their Relative Transcription Activities (RTAs). Some ligands had binding affinities in the same order of magnitude as for estradiol itself and two were less toxic than estradiol. This work also shows that the receptors can accept almost equally well isomers that have very different molecular shapes. The second part of the thesis describes an ethno-pharmacological project on Neurolaena lobata (Asteraceae), a medicinal plant used in folk medicine in Central America to treat various symptoms such as headaches, fevers and skin diseases. Isolation and identification of five sesquiterpene lactones (5) are described and bioassays results for inflammation are presented. All compounds isolated from the leaves of N. lobata were potent inhibitor of the pro-inflammatory cytokine TNFα, some even more than the positive control Parthenolide. The final section of this work presents the first phytochemical study of the plant Leretia cordata (Icacinaceae). Characteristic secondary metabolites and the potential biological activities of the isolated compounds were identified. Four known complex polyoxygenated diterpenoids (6) with known anti-cancer properties have been isolated.